Stress and coping among consultant physicians working in Saudi Arabia - Alosaimi, Fahad Dakheel; Alawad, Hossam Saleh; Alamri, Ayedh Khalaf; Saeed, Abdullah Ibrahim; Aljuaydi, Khalid Ayidh; Alotaibi, Alwaleed Sami; Alotaibi, Khalid Munawir; Alfaris, Eiad Abdelmohsen (Annals of Saudi medicine, 2018)
Exposure to stressful working conditions without adequate stress-coping strategies may lead to stress and even psychiatric morbidity. There are a dearth of studies on stress-coping strategies among consultant physicians in the Arabian Gulf. Determine stress-coping strategies among consultants in Saudi Arabia and the relationship of strategies to level of stress. Analytical cross-sectional study. Conducted between November 2014 and March 2015 among physician consultants registered at the Saudi Commission for Health Specialties. Text messages were used to directly ask consultants to complete an online questionnaire. The 28-item Brief COPE inventory and the Perceived Stress Scale. 582. The consultants were largely males (71%) and Saudi (56%), and their mean age was 46.9 (7.9) years. Adaptive stress-coping strategies were more frequently used than maladaptive stress-coping strategies (68% versus 49%). Stress levels were positively correlated with maladaptive stress-coping strategies (r=0.41, P less than .001) and negatively correlated with adaptive stress-coping strategies (r=-0.09, P=.026). Religion was the most frequently reported stress-coping strategy (79.6%) while alcohol drinking or substance use was the least frequently reported stress-coping strategy (28.0%). Females used both adaptive and maladaptive stress-coping strategies more than males (P=.002 and P less than .001, respectively). Stress management education/training was positively associated with frequent use of adaptive stress-coping strategies. Physician consultants generally cope well with work stressors. Nevertheless, there is still a critical need for stress management programs targeting consultants in order to further improve coping strategies. The low response rate may negatively impact the validity and the generalizability of the current findings. The cross-sectional study design precluded the finding of any causal association. None.